2019
DOI: 10.1177/0963689719867285
|View full text |Cite
|
Sign up to set email alerts
|

The Neuroprotective Effects of Necrostatin-1 on Subarachnoid Hemorrhage in Rats Are Possibly Mediated by Preventing Blood–Brain Barrier Disruption and RIP3-Mediated Necroptosis

Abstract: Despite the substantial efforts to elucidate the role of early brain injury in subarachnoid hemorrhage (SAH), an effective pharmaceutical therapy for patients with SAH continues to be unavailable. This study aims to reveal the role of necroptosis after SAH, and explore whether the disruption of the blood–brain barrier (BBB) and RIP3-mediated necroptosis following SAH in a rat SAH model are altered by necrostatin-1 via its selective inhibition of receptor-interacting protein kinase 1 (RIP1). Sixty-five rats wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
23
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 68 publications
1
23
1
Order By: Relevance
“…Accordingly, the treatment of mice with BPA and the necroptosis inhibitor NEC-1 reversed cardiotoxic effects of BPA producing fewer hemorrhages and less inflammation. In support of our results, Chen J. et al showed that NEC-1 prevented the disruption of the brain-blood barrier reducing brain hemorrhages 75 . However, NEC-1 only induced a moderate improvement of cardiac function so the possibility of a direct effect of BPA on myocardium by a different pathway cannot be completely ruled out.…”
Section: Discussionsupporting
confidence: 91%
“…Accordingly, the treatment of mice with BPA and the necroptosis inhibitor NEC-1 reversed cardiotoxic effects of BPA producing fewer hemorrhages and less inflammation. In support of our results, Chen J. et al showed that NEC-1 prevented the disruption of the brain-blood barrier reducing brain hemorrhages 75 . However, NEC-1 only induced a moderate improvement of cardiac function so the possibility of a direct effect of BPA on myocardium by a different pathway cannot be completely ruled out.…”
Section: Discussionsupporting
confidence: 91%
“…Apart from I/R injury, the protective effect of Nec-1 has been observed in other disease models like brain hemorrhage and traumatic injury, which is related to I/R injury or I/R disease mechanism. In animal models of intracerebral/subarachnoid hemorrhage (ICH/SAH), application of Nec-1 attenuates cell death, reduces hematoma volume and improves neurological outcomes [ 37 , 55 , 136 , 137 ]. Besides, both pre-treatment and post-treatment of Nec-1 exerts protection against brain hemorrhage [ 54 , 55 ], indicating a broad therapeutic window.…”
Section: Role Of Nec-1 In Disease Modelsmentioning
confidence: 99%
“…In animal models of intracerebral/subarachnoid hemorrhage (ICH/SAH), application of Nec-1 attenuates cell death, reduces hematoma volume and improves neurological outcomes [ 37 , 55 , 136 , 137 ]. Besides, both pre-treatment and post-treatment of Nec-1 exerts protection against brain hemorrhage [ 54 , 55 ], indicating a broad therapeutic window. The underlying molecular mechanism is still not definite, but it involves oxidative stress and inflammation: for example, Nec-1 alleviates glutathione (GSH) depletion in hemin-induced cell death and inhibits NLRP3 inflammasome activation; the attenuated oxidation and inflammation ameliorates brain swelling and blood-brain barrier disruption, finally inhibits the formation of brain edema [ 54 , 55 , 138 ].…”
Section: Role Of Nec-1 In Disease Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Necrostatin-1 is a small-molecule inhibitor of necroptosis, which is characterized by its selective inhibitory impact on RIPK1 (Degterev et al, 2005(Degterev et al, , 2008. Numerous studies have recently discovered the neuroprotective effects of Nec-1, whereas the addition of Nec-1 significantly decreased the related RIPK/MLKL protein levels in necroptosis (Chen et al, 2019). Our results showed that Nec-1 administration significantly dampened the increased expression of RIPK1, RIPK3, MLKL, and pMLKL.…”
Section: Discussionmentioning
confidence: 48%